El papel del periodismo deportivo en la construcción de la identidad del Centro Deportivo Olmedo de Riobamba - Urco Tustón, Kevin Stalin (2026)
The objective of this research is to analyze the role of sports journalism in the formation of the identity of the Olmedo Sports Center in Riobamba, through media representations and its relationship with the perception of fans and the local community. The importance of this approach lies in the need to address the influence of the news media on the symbolic configuration of the collective imaginary of sports institutions beyond their journalistic function. Therefore, it is intended to address how sports media not only inform, but also contribute to the creation of identity discourses in sports institutions with a strong social and cultural charge. To this end, a mixed methodological approach was used, where qualitative and quantitative tools were used to address the problem. This included content analysis applied to the club's media publications, semi-structured interviews with journalists and sports communicators, and surveys of fans and fans at the local level. Thanks to triangulation, it was possible to compare the results of the analysis with theoretical sections and allowed the alternative opinions of the interviewees to be assessed.